2011
DOI: 10.1038/hdy.2010.133
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic male sterility in Mimulus hybrids has pleiotropic effects on corolla and pistil traits

Abstract: The mechanisms underlying genetic associations have important consequences for evolutionary outcomes, but distinguishing linkage from pleiotropy is often difficult. Here, we use a fine mapping approach to determine the genetic basis of association between cytonuclear male sterility and other floral traits in Mimulus hybrids. Previous work has shown that male sterility in hybrids between Mimulus guttatus and Mimulus nasutus is due to interactions between a mitochondrial gene from M. guttatus and two tightly lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
(71 reference statements)
0
25
1
Order By: Relevance
“…Flower size on the other hand seems to be determined more by the level of male functionality, possibly due to a strong developmental correlation between the stamens and petals, because of a genetic linkage or pleiotropic effects (Raab and Koning, 1988;Schultz, 2003;Barr and Fishman, 2011), even though we did not find a correlation between the number of functional anthers and flower size within the intermediates.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Flower size on the other hand seems to be determined more by the level of male functionality, possibly due to a strong developmental correlation between the stamens and petals, because of a genetic linkage or pleiotropic effects (Raab and Koning, 1988;Schultz, 2003;Barr and Fishman, 2011), even though we did not find a correlation between the number of functional anthers and flower size within the intermediates.…”
Section: Discussioncontrasting
confidence: 52%
“…In fact, female flowers are almost always smaller than hermaphrodite flowers (reviewed in Delph, 1996 andShykoff et al, 2003;e.g. Bai et al, 2011;Barr and Fishman, 2011;Cuevas and López, 2011;Griffin and Byers, 2012;Blank et al, 2014;Cuevas et al, 2014) and/or they produce less nectar and pollen, leading to lower pollinator visitation rates (Delph, 1996;Ashman, 2000;Bai et al, 2011). On the other hand, the smaller size and number of flowers of female plants may also render them less attractive to enemies like florivores or seed herbivores, leading to a relatively higher seed output in females than hermaphrodites (Marshall and Ganders, 2001;Ashman, 2002;Asikainen and Mutikainen, 2005a;Collin and Shykoff, 2009;Clarke and Brody, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this possibility, c. 40% of Capsella F 2 flowers exhibited homeotic abnormalities (often seen in hybrid CMS), and the largest QTL for floral aberration (table 2 in Slotte et al, 2012) overlapped with the leading QTLs for both male and female reproductive traits. Our results in Mimulus (Barr & Fishman, 2011; this study) suggest that sterility commonly affects floral traits in hybrids, and argue for the explicit consideration of the pleiotropic effects of hybrid sterility in future investigations of the genetic basis of floral trait divergence.…”
Section: Researchmentioning
confidence: 96%
“…In measuring floral traits, we also discovered that a fraction of M. parishii 9 M. lewisii F 2 hybrids were completely male sterile, making deformed anthers with little or no pollen. Male sterility, and especially hybrid anther sterility (Barr & Fishman, 2011), often has pleiotropic effects on floral morphology (reviewed in Chase, 2007), so we then asked whether anther sterility QTLs were coincident with (and probably causal of) floral QTLs. If so, this could be a general confounding factor in estimating the genetic architecture of floral traits.…”
Section: Introductionmentioning
confidence: 99%
“…Remember that to spread, females must benefit from the loss of pollen production by producing more or better seeds. Barr and Fishman (2011) showed that male sterility had negative pleiotropic effects on corolla size, male-sterile plants had smaller flowers, but also positive effects on female traits such as the style length and thus better exposure of style and stigma, and a marginal increase in seed production. The question remains how restorer alleles succeeded in spreading to the whole species until their complete fixation in the species, since only interspecies crosses revealed male sterility.…”
Section: Genome Evolution and Gynodioecymentioning
confidence: 98%